BELIEFS, BARRIERS, AND CYCLICAL PATTERN OF CARE: EXPLAINING TREATMENT PATHWAYS OF VESICOVAGINAL FISTULA PATIENTS IN EBONYI AND PLATEAU STATES, NIGERIA - Chioma Efam, Okwuchi; H. Yale, Nalong (African Journal of Social and Behavioural Sciences, 2026)
Vesicovaginal Fistula (VVF), which is an abnormal opening between the bladder and the vagina that results in uncontrollable leakage of urine, remains a major public health concern among women in sub-Saharan Africa. In Nigeria, VVF is perceived to be caused by multiple factors, including obstetric complications, spiritual forces and bad omen. These perceptions strongly influence the treatment options women pursue, resulting in diverse treatment pathways. The study adopted the Health Belief Model as its theoretical framework and employed a comparative qualitative design. Data were generated through in-depth interviews and key Informant Interviews involving forty (40) VVF patients (20 per state) and eight (8) healthcare professionals (4 per state) in Ebonyi and Plateau States. The data were analysed using thematic content-analysis. Findings revealed multiple treatment pathways involving repeated movements between home remedies, traditional healers, faith-based centres, primary health care facilities, hospitals and specialized VVF centres. Key factors influencing treatment pathways included perceived causes of VVF, financial constraints, place of delivery and distance to health facilities. Cues to action included a doctor’s referral, media publicity and significant others. Although some contextual differences were observed between the two states, treatment pathways were largely similar. The findings contribute to understanding sociocultural determinants of delayed VVF treatment and inform future sensitization efforts on the causes and appropriate treatment of VVF to reduce delays and improve health outcomes.